DEVELOPMENT OF DISCOVERY LEARNING-BASED SCIENCE INSTRUCTIONAL MATERIALS TO ENHANCE JUNIOR HIGH SCHOOL STUDENTS’ NUMERACY SKILLS - Hanna Rohana; Murti Kusuma Wirasti; Maria Paristiowati (RADJA PUBLIKA, 2026)
Science learning packages that explicitly integrate numeracy skills remain limited in development for junior high school level, particularly on the topic of Vibration and Waves. This study aimed to develop and examine the feasibility of a Discovery Learning-based science learning package oriented toward strengthening the numeracy skills of eighth-grade junior high school students. The study employed the Dick & Carey development model, with the reporting focus limited to the expert validation stage as part of formative evaluation. The developed products consisted of a teaching module, instructional materials, student worksheets (LKPD), and assessment instruments on the topic of Vibration and Waves. Validation was conducted by three experts: a content expert, an instructional design expert, and a media expert. The validation instrument used a five-point Likert scale, with feasibility percentages analyzed based on Sugiyono’s (2013) criteria. The validation results showed that the learning package obtained feasibility percentages of 89.3% (content expert), 97.24% (instructional design expert), and 82.9% (media expert), all of which fell into the Very Feasible category. The developed Discovery Learning-based science learning package was declared valid and feasible for use in the learning trial stage.